ULTRA PERFORMANCE LIQUID CHROMATOGRAPHY (UPLC) METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF LALANYL-L-GLUTAMINE IN PHARMACEUTICAL DOSAGE FORM (INFUSIONS). : Pharmaceutical Science-Pharmaceutical Analysis - N. WADIA, DEVANG.; T. DESAI, HEMANT. (International Journal of Life Science and Pharma Research, 2012)
A simple, precise, accurate and validated reverse phase UPLC method has been developed for the estimation of L-Alanyl L-Glutamine (20% w/v) in infusion. The quantification was carried out using amino-bonded silica gel column, packed with octadecylsilane (2.1 mm × 100 mm, 1.7 μm) and the mobile phase used was a mixture of acetonitrile and 0.05 M phosphate buffer, pH 4, (70:30) at a flow rate of 0.25 ml / min. The detection wavelength was 215 nm and column temperature was 400C. The retention time was found to be 0.77 min. The results obtained showed a good agreement with the declared content. Recovery values for L-Alanyl -LGlutamine were 99.19 - 100.82 %. The proposed method is reliable, rapid, precise, selective and may be used for the quantitative analysis of L-Alanyl -L-Glutamine in infusions